2006
DOI: 10.2139/ssrn.917581
|View full text |Cite
|
Sign up to set email alerts
|

Do Institutions Matter for FDI? A Comparative Analysis for the MENA Countries

Abstract: Abstract. The paper analyses the underpinning factors of foreign direct investments• Vittorio Daniele is Researcher in Economic Policy at the University Magna Graecia of Catanzaro; email: v.daniele@unicz.it. Ugo Marani is Full professor of Economic Policy at the University Federico II of Naples; E-mail: marani@unina.it. The present work is the result of a common reflection; nonetheless, sections 1, 2.1 and 4 can be attributed to Ugo Marani, sections.2.2. and 3 to Vittorio Daniele. The authors would like to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
0
17
0
4
Order By: Relevance
“…), thus affecting the expected return on investment [2]. The scholars found that institutional quality is significantly positively correlated with FDI, and FDI is more inclined to superior institutional environment [3] [4] [5]. However, the above conclusion is not supported by all studies, Conversely, some scholars found that China's OFDI is better than that in the regions and countries with high political risks and poor institutional quality [6] [7] [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…), thus affecting the expected return on investment [2]. The scholars found that institutional quality is significantly positively correlated with FDI, and FDI is more inclined to superior institutional environment [3] [4] [5]. However, the above conclusion is not supported by all studies, Conversely, some scholars found that China's OFDI is better than that in the regions and countries with high political risks and poor institutional quality [6] [7] [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…His empirical results have shown that what really matters are the rules and games in a society. Daniele & Marani [2006] discuss potential channels through which institutions may affect the level of investment. First, the presence of good institutions tends to improve productivity, and subsequently stimulates investment, regardless whether domestic or external.…”
Section: Institutions and Fdimentioning
confidence: 99%
“…During the nineties, FDI represented an average of 0.9% of the GDP in MENA countries, against 2.5% in African countries, 3.8% in Eastern Asia and 4.5% in Latin America (Sekkat 2004). A few years later, and despite a fast increase of the FDI inflows to Tunisia, Morocco and Egypt, such a weakness in attracting investment was still underlined by the studies of Chan and Gemayel (2004), Iqbal and Nabli (2004), Sekkat (2004) or Daniele and Marani (2006). In addition, Iqbal and Nabli (2004) or Noland and Pack (2007) also showed that the degree of integration to the global production chains is very limited in spite of the closeness to the European market.…”
Section: Introductionmentioning
confidence: 99%
“…11 Cross-sectional studies have not produced particularly consistent evidence about what explain both the poor performance of MENA countries in attracting FDI and the weakness of the spillover effect from FDI. Furthermore, the weakness of the legal and administrative environment in the MENA countries has been underlined as a major hindrance to growth by the recent surveys of Alessandrini (2000), Daniele and Marani (2006), Chan andGemayel (2004), Be´nassy-Que´re´et al (2005) or Sekkat (2004) that all underline the necessity of furthering the reforms in that field.…”
Section: Introductionmentioning
confidence: 99%